Ionization inhibition in a polyol/water system for boosting H2 generation from NaBH4. Issue 1 (24th December 2020) - Feng, Lili; Wang, Cong; Xu, Jinrong; Fang, Mingwei; Shi, Yu; Xie, Lei; Zheng, Jie; Li, Xingguo
Abstract : A different polyol/water system was constructed to promote the alcoholysis of NaBH4 . The ionization of reaction products is inhibited, thus boosting H2 generation. Abstract : Alcoholysis and hydrolysis of NaBH4 to produce H2 offer attractive routes to sustainable development with high energy density and environmentally-friendly features. However, the productivity is often limited by the increased alkalinity of the reaction system and the deactivation of catalysts. Here, we present a novel strategy of constructing a polyol/water composite system to promote catalyst free alcoholysis of NaBH4 while inhibiting the ionization of reaction products. The polyol/water system exhibits a NaBH4 conversion of more than 90% in less than 60 min, especially when the erythritol/water system is employed with a conversion of 96% in 80 min. Further study shows that erythritol participates in the reaction and the ionization of reaction products is inhibited by erythritol. Moreover, the analysis of reaction products and control group results reveal that erythritol indeed inhibits the basicity enhancement of the reaction system via reacting with NaB(OH)4 . By adjusting the volume of water in the polyol/water system, a quasi-solid phase reaction system is developed for practical applications, which shows an excellent NaBH4 conversion of 94% and high hydrogen storage gravimetric density of 3.9 wt%.